Polymer interaction of the genes SHY2 and MSG1, NPH4 and IAR2 in the inheritance of the Arabidopsis thaliana (L.) Heynh. root system - S. G. Hablak (Вавиловский журнал генетики и селекции)
Roots branching regulation is an important adaptive mechanism for the adaptation of plants to root environments. Elucidation of the genetic mechanisms involved in increase in the degree of plant root branching is essential in improving the responsiveness of crops to supply elements. The aim was to study the interaction of the genes SHY2 and MSG1, NPH4 and IAR2 as attributes of the root system of A. thaliana are inherited. By crossing plants of the mutant lines shy2-2×msg1-2, nph4-1×iar2-1, a segregation in F2 was observed, suggesting an interaction between the polymer SHY2 and MSG1, NPH4 and IAR2 genes. The segregation ratio of the phenotypes in F2 is 15:1. The results presented are of interest for practical use of the economically valuable trait «branching roots» in plant breeding to create varieties and hybrids with the desired properties of mineral nutrition. Our data indicate that the ability of plant roots to increase the degree of branching depends on individual genes and can be inherited through polymer gene interactions. Knowing the polymeric nature of inheritance in the root system, the length of lateral roots in the interaction of genes can be combined by crossing genes and increase the degree of branching of the roots from cultivated plants to create agrochemically effective varieties and hybrids.